Effects of Massage Therapy on Anxiety in Heart Disease Patients: A Systematic Review - Kristinawati, Beti; Handika, Bintang Viga; Rizkiawan, Ardhu; Mardana, Nyofan Wahyu; Wijayanti, Nove Wiand Dwi (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Patients with heart disease often experience anxiety as a response to physiological changes, and massage therapy is one of the alternative treatments available to alleviate this condition. Although the benefits of massage therapy in reducing anxiety are well recognized, there is a lack of focused research evaluating its specific effects on individuals with heart disease.Purpose: This review aims to systematically assess the effects of massage therapy on anxiety levels in patients with heart disease.Methods: A systematic review of the literature published between January 1, 2000, and December 31, 2020, was conducted using the PubMed, ScienceDirect, Scopus, CrossRef, and Google Scholar databases. Seventeen studies that met the inclusion criteria were selected for review. The quality of the included studies was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool, and the findings were synthesized narratively.Results: The review indicates that massage therapy has a positive effect on reducing anxiety in patients with heart disease. Various massage techniques consistently demonstrated significant anxiety-reducing outcomes. However, the heterogeneity of massage therapy techniques limits the ability to draw conclusions about the comparative effectiveness of existing studies, particularly in reducing anxiety levels.Conclusion: Based on this systematic review, massage therapy appears to significantly reduce anxiety levels in patients with heart disease, including both surgical and non-surgical populations. This review highlights the value of integrating massage therapy into holistic patient care, especially for managing anxiety and enhancing comfort.